CREATING POSITIVE LEARNING ENVIRONMENT THROUGH WORK-LIFE BALANCE BASED HUMAN RESOURCE DEVELOPMENT - Rozi, Fathor; Kamalia, Siti (Nurul Jadid University, 2023)
Management often needs to be aligned with human resources. Human resource management is a factor in the success of an institution. The impact of this misalignment will affect the success of the institution. Human resources play a significant role in realizing the success of an institution in achieving its goals. Therefore this study aims to analyze the development of work-life balance based on human resources. This research method uses case studies at Madrasah Aliyah Nurul Jadid using qualitative interviews and documentation. This research will explain how Madrasah Aliyah Nurul Jadid develops a work-life balance based on human resource management. So that educators can divide their time between families and institutions to get maximum results. The results of this study indicate that the development of human resources in Madrasah Aliyah Nurul Jadid has been carried out in the form of; 1) Training Development, 2) Spiritual Development, 3) Talent Development, 4) Performance Development, and 5) Leadership Development.